2020
DOI: 10.1007/s12182-020-00495-1
|View full text |Cite
|
Sign up to set email alerts
|

Shale gas reservoir modeling and production evaluation considering complex gas transport mechanisms and dispersed distribution of kerogen

Abstract: Stimulated shale reservoirs consist of kerogen, inorganic matter, secondary and hydraulic fractures. The dispersed distribution of kerogen within matrices and complex gas flow mechanisms make production evaluation challenging. Here we establish an analytical method that addresses kerogen-inorganic matter gas transfer, dispersed kerogen distribution, and complex gas flow mechanisms to facilitate evaluating gas production. The matrix element is defined as a kerogen core with an exterior inorganic sphere. Unlike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Based on the above analyses, the developed model is capable of describing anisotropic swelling and anisotropic permeability evolution of coal. Since coal and shale share many similarities, such as gas adsorption, stress sensitivity, and gas rarefaction effects in narrow flow channels, 68 the proposed permeability model can be used to simulate shale anisotropic permeability evolution behavior. One can use three sets of equivalent fractures to represent shale fracture (pore) networks.…”
Section: Validation Of the Permeability Model Under Constant Confinin...mentioning
confidence: 99%
“…Based on the above analyses, the developed model is capable of describing anisotropic swelling and anisotropic permeability evolution of coal. Since coal and shale share many similarities, such as gas adsorption, stress sensitivity, and gas rarefaction effects in narrow flow channels, 68 the proposed permeability model can be used to simulate shale anisotropic permeability evolution behavior. One can use three sets of equivalent fractures to represent shale fracture (pore) networks.…”
Section: Validation Of the Permeability Model Under Constant Confinin...mentioning
confidence: 99%
“…However, the flow behavior in a tight gas reservoir is complex. It has been found that such a reservoir has a threshold pressure gradient [9,10]; the permeability in a tight gas reservoir may change with pressure and exhibits a stress-sensitive effect during the production process [11,12]; the proppant embedment issues in the hydraulic fractures of a tight reservoir may affect the gas production [13]; the temperature and pressure may affect the imbibition recovery for tight or shale gas reservoir [14]; the tight gas production may be seriously reduced by water blockage [15][16][17]; the dispersed distribution of kerogen within matrices may affect the production evaluation [18]; sulfur precipitation and reservoir pressure-sensitive effects may affect the permeability, porosity and formation pressure [19]; the micro-scale flow mechanism, such as Knudsen diffusion, slippage effect, and adsorption, can be difficult to describe quantitatively [20,21]. All these complexities associated with tight gas reservoirs make it difficult to build an accurate mathematical model to predict gas flow in tight gas reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…No matter directly or indirectly, they are the inputs that needed in the all stages of production performance analysis [1][2][3][4][5]. Reservoir evaluation relies on amount of mathematical solutions of the flow equations for reservoir or well characterization, among which pressure transient analysis and well productivity evaluation are the mostoften-used techniques in the petroleum engineering [6][7][8][9]. The main purpose of pressure transient analysis is to collect the shut-in pressure data under controlled well rate conditions to determine reservoir and fracture parameters and estimate reservoir size [10].…”
Section: Introductionmentioning
confidence: 99%